Learning Model of Local Cultural Values Based on Augmented Reality for Social Science Education in Elementary School - Sudrajat, Ajat; Darojat, Ojat; Kustandi, Cecep; Purwatiningsih, Anastasia Sri Endang; Mikdar, Syaeful; Thalib, Jasmi Bin Abu (International Journal of Social Learning (IJSL), 2024)
Integrating digital technology and local cultural values is needed in the learning process to instill feelings of tolerance and introduce diverse cultures to students. This research aims to analyze the steps of developing an augmented reality-based local cultural values learning model for social education learning in elementary schools. This development method is conducted through R&D adapted from Borg and Gall. This research collaborated with two teachers and ten students in the fifth-grade elementary schools in Lebak Regency, Banten.  Data were collected through in-depth interviews, observations, and questionnaires. The results showed that local cultural values can be integrated with augmented reality technology to introduce cultural diversity to students in elementary schools. This research has implications for the character of elementary school students through the cultivation of local cultural values, namely caring for the environment, obeying the law, truthfulness, being able to collaborate, and understanding the concept of purity.